Flu shots, mammograms, and the perception of probabilities - Katherine Grace Carman; Peter Kooreman (Institute for the Study of Labor (IZA), 2011)
We study individuals' decisions to decline or accept preventive health care interventions such as flu shots and mammograms. In particular, we analyze the role of perceptions of the effectiveness of the intervention, by eliciting individuals' subjective probabilities of sickness and survival, with and without the interventions. Respondents appear to be aware of some of the qualitative relationships between risk factors and probabilities. However, on average they have very poor perceptions of the absolute probability levels as reported in the epidemiological literature. Perceptions are less accurate if a respondent is female and has no college degree. Perceived probabilities significantly affect the subsequent take-up rate of flu shots and mammograms.
urn:nbn:de:101:1-201106013890
Keywords: I10; 330; preventive health care; probability perceptions